Studies of an epoxy-compatibilized poly(phenylene sulfide)/polycarbonate blend - Choi, J; Lim, S; Kim, J; Choe, CR (ELSEVIER SCI LTD, 1997)
Tensile properties, morphology and thermal behaviour of a poly(phenylene sulfide) (PPS)/polycarbonate (PC) binary system and an PPS/PC/epoxy ternary system were investigated. It was observed that the viscosity-average molecular weight (M-v) of the PC fraction was decreased during the melt binding of PC with PPS. This phenomenon was more pronounced as PPS concentration increased. By melt blending PPS and PC with epoxy as a compatibilizer, a shift of glass transition temperature of PC to a lower temperature could be somewhat prevented. It is suggested that epoxy coupled the degraded PC chains generated by blending with PPS. In contrast to PPS/PC binary system, phase separation in the PPS/PC/epoxy ternary system could hardly be observed in the scale of scanning electron micrographs. The tensile strength and tensile modulus of PPS/PC/epoxy system were remarkably improved (more than 100%) compared to those of the epoxy-free system. It was found that the improvement in tensile properties is mainly due to the homogeneous morphology by blending a small amount of epoxy with PPS and PC. (C) 1997 Elsevier Science Ltd.
Keywords: POLYCARBONATE; BISPHENOL; SULFIDE); BEHAVIOR